PENGARUH PERSEPSI KEBERMANFAATAN, PERSEPSI KEMUDAHAN, KEPUASAN, KECEPATAN, KEAMANAN DAN KERAHASIAAN TERHADAP PENGGUNAAN FASILITAS E-FILING SEBAGAI SARANA PENYAMPAIAN SPT MASASECARA ONLINE DAN REALTIME BAGI WAJIB PAJAK BADAN DI DUMAI - Nurjannah '; M. Rasuli '; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted to test whether the perceived of usefulness, perceived of ease, satisfaction, speed, and security and secrecy affect the use of e-filing facility. Research was conducted on corporate taxpayers who take advantage of e-filing are listed on KPP Pratama Dumai. The number of respondents in this research is as much as 70 respondents. The analytical method used in this research is multiple linear regression analysis with SPSS version 19.0.0. The results of the research showed that the perceived of ease, satisfaction, and speed affect the use of e-filing facility. The results also show that the perception of the usefulness as well as security and secrecy does not affect the use of e-filing facility. The coefficient of determination by the five variables in this study affect the dependent variable together amounted to 79.2%, while 20.8% is influenced by other variables not included in this regression model.Keywords : E-filing, Perceived of Usefulness and Ease, Satisfaction, Security and Secrecy